Desensitisasi Sistematis dengan Relaksasi Zikir untuk Mengurangi Gejala Kecemasan pada Kasus Gangguan Fobia - Anisa Fitriani; Ratna Supradewi (Faculty of Psychology, Universitas Semarang, 2019)
Phobia is anxiety disorders in the form of excessive and irrational fear to certain objects or situations. Phobia symptoms can interfere with daily activities, such as muscle tension, trembling, cold sweat, dizziness, nausea, panic, and various other discomforts. This study aimed to look at the effect of systematic desensitization therapy combined with dhikr relaxation to reduce anxiety levels in people with phobias. The method used in this research was an experiment with pretest and posttest one group design. Data obtained by phobia anxiety scale Severity Measure for Specific Phobia-Adult, observation during therapy process, interviews, and measurement of Subjective Units of Discomfort Scale (SUDS). Subjects consisted of two people, soursop phobia and needle phobia. The results showed that systematic desensitization therapy with dhikr relaxation can reduce physical and psychological anxiety symptoms, so that the subject's phobia level is reduced, from severe phobia to moderate phobia and mild phobia. Keywords: systematic desensitization, dhikr, phobia, anxiety, relaxationDaftar PustakaAmerican Psychiatric Association. (2013). Diagnostic and Statistical Manual of Mental Disorders Fifth Edition. England: American Psychiatric Publishing.Arikunto, S. (2010). Prosedur Penelitian: Suatu Pendekatan Praktik. Jakarta: Rineka Cipta.Atrup, A., & Fatmawati, D. (2018). Hipnoterapi Teknik Regression Therapy Untuk Menangani Penderita Glossophobia Siswa Sekolah Menengah Pertama. Pinus, 3(2), 138 149.Azmarina, R. (2015). Desensitisasi Sistematik Dengan Zikir Tasbih Untuk Menurunkan Simtom Kecemasan Pada Gangguan Fobia Spesifik. Humanitas, 12(2), 90 104. https://doi.org/10.26555/humanitas.v12i2.3836Bukhori, B. (2008). Zikir Al-Asma al-Husna Solusi atas Problem Agresivitas Remaja. Semarang: Rasail Media.Craske, M., Wittchen, U., Bogels, S., Stein, M., Andrews, G., & Lebeu, R. (2013). Severity Measure for Specific Phobia-Adult. Retrieved from American Psychiatric Association website: https://www.psychiatry.org/psychiatrists/practice/dsm/educational-resources/assessment-measuresCreswell, J. W. (2010). Research Design: Pendekatan Kualitatif, Kuantitatif, dan Mixed. Yogjakarta: PT Pustaka Pelajar.Firosad, A. M., Nirwana, H., & Syahniar, S. (2016). Teknik Desensitisasi Sistematik untuk Mengurangi Fobia Mahasiswa. Konselor, 5(2), 100 107. https://doi.org/10.24036/02016526546-0-00Hawari, D. (2010). Al-Qur an Ilmu Kedokteran Jiwa dan Kesehatan Jiwa. Jakarta: Balai Penerbit Fakultas Kedokteran Universitas Indonesia.Hendriyani, R., & Ahadiyah, A. (2012). Faktor-Faktor yang Menyebabkan Pediophobia (Studi Kasus pada Penderita Pediophobia). 4(2), 1 6.Herdiansyah, M., & Sumampouw, N. J. (2018). Systematic Desensitization for Treating Specific Phobia of Earthworms: An In Vivo Exposure Study. 135(Iciap 2017), 340 349. https://doi.org/10.2991/iciap-17.2018.33Karfe, B., & Atim, A. (2018). Effects of Systematic Desensitization and Study Skills Counselling Therapies on Test-Anxiety in Physics among Senior Secondary School Students in Jalingo, Taraba State. 18(5).Komalasari, G., Wahyuni, E., & Karsih. (2011). Teori dan Teknik Konseling. Jakarta: Indeks.Martin, G., & Pear, J. J. (2015). Behavior Modification: What It Is And How To Do It. Canada: Psychology Press.Maslim, R. (2013). Buku Saku Diagnosis Gangguan Jiwa Rujukan Ringkasan dari PPDGJ-III dan DSM-5. Jakarta: Ilmu Kedokteran Jiwa FK-Unika Atmajaya.Nanik, & Gunawinata, V. A. R. (2011). Terapi Perilaku Untuk Fobia Lift. Jurnal Psikologi, 5(2), 215 224.Nelson, J. R. (2011). Teori dan Praktik Konseling dan Terapi Edisi Keempat. Yogyakarta: Pustaka Pelajar.Nevid, J. S., Rathus, S. A., & Greene, B. (2005). Psikologi Abnormal Jilid 1. Jakarta: Erlangga.Palmer, S. (2010). Konseling dan Psikoterapi. Yogyakarta: Pustaka Pelajar.PaloÈ™, R., & V ®È™cu, L. (2014). Anxiety, Automatic Negative Thoughts, and Unconditional Self-Acceptance in Rheumatoid Arthritis: A Preliminary Study. ISRN Rheumatology, 2014, 1 5. https://doi.org/10.1155/2014/317259Patimah, I., Suryani, & Nuraeni, A. (2015). Pengaruh Relaksasi Zikir terhadap Tingkat Kecemasan Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisa. Jurnal Keperawatan Padjadjaran, 3(1). https://doi.org/10.24198/jkp.v3i1.95Saidah, K. (2016). Perkembangan Fisik dan Sosio-Emosi pada Siswa dengan Gejala Fobia Spesifik: Studi Kasus pada Siswa dengan Gejala Fobia Nasi. Ar-Risalah, 18(2), 66 72. https://doi.org/10.1017/CBO9781107415324.004Suryani. (2013). Salat and Dhikr to Dispel Voices: The Experience of Indonesian Muslim with Chronic Mental Illness. Malaysian Journal of Psychiatry. Retrieved from http://www.mjpsychiatry.org/index.php/mjp/article/view/225Willis, S. (2004). Konseling Individual: Teori dan Praktek. Bandung: Alfabeta.